Improving students’ critical thinking skills using time bar media in mathemathics learning in the third-grade primary school - Wahyu Purwaningsih; Muhammad Nur Wangid (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
This study aims to improve the students’ critical thinking skills using time bar media in mathema-tics learning for in grade IIIA of State Primary School Kotagede I. It used classroom action research as design by Kemmis and McTaggart. The subjects of this research were grade 3th State Primary School Kotagede I with a total of 30 students. The data were collected through observation, written tests, and interviews. The research instrument used was the teacher's activity observation sheet in mathematics learning, written test questions, and interview guides for teachers and students. The instrument of the test each test question there are 6 items in the description. The obtained data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the use of time bar media in mathematics learning could improve students' critical thinking skills. The critical thinking skills covered: providing simple explanations, building basic skills, concluding, providing further explanations, and arranging strategies and tactics. The increase in students' critical thinking skills was seen based on the test results in the pre-action (43%) which increased to 80% in the first cycle and increased to 90% in the second cycle.